2017
DOI: 10.1186/s11671-016-1769-y
|View full text |Cite
|
Sign up to set email alerts
|

XPS Depth Profile Analysis of Zn3N2 Thin Films Grown at Different N2/Ar Gas Flow Rates by RF Magnetron Sputtering

Abstract: Zinc nitride thin films were grown on fused silica substrates at 300 °C by radio frequency magnetron sputtering. Films were grown at different N2/Ar flow rate ratios of 0.20, 0.40, 0.60, 0.80, and 1.0. All the samples have grain-like surface morphology with an average surface roughness ranging from 4 to 5 nm and an average grain size ranging from 13 to16 nm. Zn3N2 samples grown at lower N2/Ar ratio are polycrystalline with secondary phases of ZnO present, whereas at higher N2/Ar ratio, no ZnO phases were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…All layers were found to be n-type and display large electron concentrations, as commonly observed for Zn 3 N 2 . 27,33,34,37,38,41,42 This may indicate a main donor associated to nitrogen vacancies (or zinc interstitials) and an increased desorption of nitrogen during growth, which is in agreement with the decrease of the growth rate (see Table I). Another possible reason for the increase of electron concentration as a function of substrate temperature may be the enhanced incorporation of residual oxygen at high temperatures (e.g.…”
Section: Electrical Properties Of Zn 3 Nsupporting
confidence: 65%
See 1 more Smart Citation
“…All layers were found to be n-type and display large electron concentrations, as commonly observed for Zn 3 N 2 . 27,33,34,37,38,41,42 This may indicate a main donor associated to nitrogen vacancies (or zinc interstitials) and an increased desorption of nitrogen during growth, which is in agreement with the decrease of the growth rate (see Table I). Another possible reason for the increase of electron concentration as a function of substrate temperature may be the enhanced incorporation of residual oxygen at high temperatures (e.g.…”
Section: Electrical Properties Of Zn 3 Nsupporting
confidence: 65%
“…Furthermore, it seems to be difficult to fabricate non-degenerate Zn 3 N 2 thin films with carrier concentrations below 10 19 cm -3 , 27,33,34,37,41,42 which lead to a Burstein-Moss shift of the absorption edge that could have caused an overestimation of the band-gap as well. 43,44 Nevertheless, Zn 3 N 2 films show generally quite large electron mobilities in the range of 100 cm²/Vs, probably due to the low reported electron effective mass of 0.08 m 0 , 42 making it an attractive candidate as active layer for TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…This is further confirmed in the Zn 2p spectrum of the sample which is consistent with the one of ZnPc ( Figure S4, Supporting Information) and does not show contributions from ZnO bonds [38] or nitride-like bonds. [39] Interestingly, even for samples synthesized at higher temperature, namely 60Li_900(Zn 2+ ) and 60Li_1000(Zn 2+ ), the Zn 2p spectrum does not change, except for the decreasing Zn content obtained with increasing synthesis temperature, pointing out that the formation and retaining of ZnN 4 sites are possible (at least) up to 1000 °C. In all synthesized samples, a smaller contribution arising from ZnCl bonds is also present.…”
Section: Imprinting Ndcs By Zn 2+ Templating (Zn-n-c)mentioning
confidence: 93%
“…According to the Al-Kuhaili et al the NiFC composite consist Ni-O functionalities which indicates that the air gun drying caused slight oxidation of Ni nanoplate [ 15 ]. A binding energy of Fe2p located at 711.18 eV specifies that the form iron oxide has Fe 3+ while the Zn2p position implies the presence of Zn-O, and Zn-N functional groups which are from oxidation and CTAB [ 16 , 17 ]. Biesinger et al reported that the binding energy position of Co in the composite indicates that it consists Co-O functional groups which is due to oxidation of Co nanoplate ( Figure 3 and Table 1 ) [ 18 ].…”
Section: Resultsmentioning
confidence: 99%